(untitled) (Journal Of Educational and Psychological Researches, 2011)
The first chapter includes introduce the research and the problem of the research that there are negligence of some educational institutions and schools management , some parents and supervisors .Also there are some educators who believes that school activities are obstacles means to learning and prevent pupils from studying and understanding the subjects. That may due to social , psychological and educational reasons The purposes of the researches come from the reports of supervision visits which indicate a lot of difficulties faced by pupils and teachers related to education activities and its influence on in education and the necessity of indentify these difficulties and remedy them . The importance of the research is in the scientific benefit , suspense , psychological and social fulfillment ,good competition and behavior development . The research aims to identify the role of education activities which affirm the studying subjects for the pupils of primary stage and limited to all activities of primary stages from Ministry of Education which accompany the curriculums for all years . School activities is identified as the learning practices in which the energies and talents are invested correctly .School education activities is a group of programs planned by education bodies by central level and local level in teaching areas and provide and provide human and financial abilities .to integrate with teaching programs .